2013
DOI: 10.1002/anzf.1036
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Approaches to Family Systems Supervision: Differentiation of Self

Abstract: Many systems approaches speak to the importance of respectful mutual curiosity in supervision rather than linear teacher-learner didacticism. This paper provides an overview of collaborative approaches to supervision in family therapy. It then focuses on Bowen family systems and encouraging differentiation in the relationship process between supervisor and supervisee as a useful approach towards equal collaboration. The authors use case examples to illustrate what impedes and fosters mutuality in the supervisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Through collaborative supervision, supervisors and supervisees can build new knowledge. Thus, it performs an effective supervision activity (da Silva Pinheiro et al, 2014; Lau et al, 2019; MacKay & Brown, 2013). This finding is also in line with the experiment result of Wiyono et al (2015) which showed that collaborative active supervision based on humanistic principles is very effective in increasing teacher professional competence.…”
Section: Discussionmentioning
confidence: 99%
“…Through collaborative supervision, supervisors and supervisees can build new knowledge. Thus, it performs an effective supervision activity (da Silva Pinheiro et al, 2014; Lau et al, 2019; MacKay & Brown, 2013). This finding is also in line with the experiment result of Wiyono et al (2015) which showed that collaborative active supervision based on humanistic principles is very effective in increasing teacher professional competence.…”
Section: Discussionmentioning
confidence: 99%
“…A lot has been written about the power dynamics in the supervisor–supervisee relationship (e.g., Burck & Daniel, ; Todd & Storm, ), and often a collaborative relationship is favored in which the supervisor is at the service of the supervisee's process (e.g., Aducci & Baptist, ; Fine & Turner, ; MacKay & Brown, ). In the TIC method, the supervisor's main focus is not on noticing mistakes made by the supervisee, or on correcting the supervisee's practice or reflections.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, it has received increasing attention in Australia and New Zealand, with a dedicated training centre in the theory started in 2004 and culminating in the development of an Australian AAFT‐accredited training program specialising in this approach (the Family Systems Institute, Sydney). Additionally, many articles on Bowen's theory have been published in this journal during this time by local and international authors 1 (see Brown, 2023a, 2023b; Collier & Villareal III, 2022; Cooper et al., 2023; MacKay, 2012, 2017; Mackay & Brown, 2013; Palombi, 2018; Papero, 2014, 2017; Wilt, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…development of an Australian AAFT-accredited training program specialising in this approach (the Family Systems Institute, Sydney). Additionally, many articles on Bowen's theory have been published in this journal during this time by local and international authors 1 (see Brown, 2023aBrown, , 2023bCollier & Villareal III, 2022;Cooper et al, 2023;MacKay, 2012MacKay, , 2017Mackay & Brown, 2013;Palombi, 2018;Papero, 2014Papero, , 2017Wilt, 2023).…”
mentioning
confidence: 99%